2022
DOI: 10.3389/fonc.2022.1018833
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a radiomics nomogram derived from Fluoride-18 PSMA-1007 PET/CT for risk stratification in newly diagnosed prostate cancer

Abstract: ObjectiveThe aim of this study was to evaluate the performance of Fluoride-18 (18F)-PSMA-1007-PET/CT radiomics for the tumor malignancy and clinical risk stratification in primary prostate cancer (PCa).Materials and MethodsA total of 161 pathological proven PCa patients in a single center were retrospectively analyzed. Prostate-specific antigen (PSA), Gleason Score (GS) and PET/CT indexes (SUVmin, SUVmax, and SUVmean) were compared according to risk stratification. Radiomics features were extracted from PCa 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Table 2 illustrates five studies utilizing PSMA PET/CT-derived radiomic models in PC staging [8,[22][23][24][25]. Three studies [22,24,25] (66.7%) utilized 68-Ga-PSMA-11 imaging and two [8,23] (33.3%) utilized Fluoride-18-PSMA-11 imaging alterations and biopsy Gleason score [25].…”
Section: Prediction Of Biopsy Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 illustrates five studies utilizing PSMA PET/CT-derived radiomic models in PC staging [8,[22][23][24][25]. Three studies [22,24,25] (66.7%) utilized 68-Ga-PSMA-11 imaging and two [8,23] (33.3%) utilized Fluoride-18-PSMA-11 imaging alterations and biopsy Gleason score [25].…”
Section: Prediction Of Biopsy Resultsmentioning
confidence: 99%
“…Among these is the prostate-specific Cancers 2024, 16, 1897 2 of 11 membrane antigen (PSMA) positron emission imaging and computerized tomography (PET/CT), which was approved by the Food and Drug Administration (FDA) in December 2020 and May 2021 for use with 68-Gallium (68-Ga) and piflufolastat (F18) in PC patients, respectively [4]. Since then, several systematic reviews have confirmed the PSMA PET/CT to more accurately detect the extent of disease [5], lymph node involvement [6,7], and distant metastases in patients newly diagnosed with PC [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…extracted radiomics features from 18 F-PSMA-1007-PET/CT imaging of primary prostate cancer to predict the tumor malignancy and clinical risk stratification. The study showed that PET/CT radiomic features alone had similar benefits as combined prostate specific antigen levels and metastatic status ( 4 ). Zhou et al.…”
Section: Identificationmentioning
confidence: 99%
“…It can extract multiple features from pathological findings and potentially define new markers of disease [183][184][185]. Radiomics has the potential to further increase the value of imaging in PC management; nevertheless, its introduction into current clinical practice is full of questions, as emphasized by several radiomic studies [186][187][188][189]. Several approaches have been proposed and standardization is the major issue.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%